Polyhydroxyalkanoate production during electroactive biofilm formation and stabilization in wetland microbial fuel cells for petroleum hydrocarbon bioconversion - Lanmei Zhao; Mengxue Sun; Can Lyu; Long Meng; Jian Liu; Bo Wang (Synthetic and Systems Biotechnology)
This study presented new insights into the sustainable conversion of total petroleum hydrocarbon (TPHC) into polyhydroxyalkanoates (PHAs) using wetland microbial fuel cells (WMFCs). The main innovations included the following two points: (1) The integration of bioelectricity generation with efficient PHA production further underscored the potential of electroactive biofilms as a sustainable platform for simultaneous TPHC biotransformation, bioelectricity recovery and PHA production. (2) The interactive dynamics of PHAs, metabolites, extracellular polymeric substances (EPS) and microorganisms during the formation and stabilization of electroactive biofilms provided novel insights into microbial strategies for carbon utilization. As the electroactive biofilm formed and stabilized, the current density enhanced significantly from 0 to 101 mA m−2, then stabilized, and finally dropped to 3.51 mA m−2. Similarly, the power density showed a trend of increasing in the initial stage, maintaining in the middle stage, and then descending in the later stage. The production of six types of PHAs was identified: poly(3-hydroxybutyrate) [P(3HB)], poly(3-hydroxyvalerate) [P(3HV)], poly(3-hydroxybutyrate-co-3-hydroxyvalerate) [P(3HB-co-3HV)], poly[(R)-3-hydroxybutyrate-co-(R)-3-hydroxyhexanoate] [P(3HB-co-3HHX)], poly(3-hydroxyhexadecanoate) [P(3HHD)] and poly(3-hydroxyoctadecanoate) [P(3HOD)], highlighting the metabolic flexibility of electroactive biofilms. The total PHA content was initially undetectable (days 0–4), gradually increased (days 4–28), rose rapidly (days 28–48), gradually increased and descended (days 48–68). The maximum PHA content of 0.664 g g⁻1 DCW achieved highlighted the dual functionality of WMFCs in bioelectricity production and PHA biosynthesis, distinguishing it from conventional MFC applications. The TPHC biodegradation ratio demonstrated a gradual increase (days 0–28), with a more pronounced rise (days 28–48), and a gradual rise to 76.1 % (days 48–68). Throughout the process, the metabolite volatile fatty acids (VFAs) produced were primarily acetate, propionate, butyrate and valerate. The trend of VFA production from days 0–56 closely followed that of TPHC biodegradation. The trend of tyrosine/tryptophan proteins in EPS was aligned with that of biofilm thickness. The strong correlation between the increase in the biofilm thickness and the intensity and peak height of tyrosine/tryptophan proteins during the first 20 days suggested that these proteins were integral to the structural integrity of the biofilms, and from days 20–64, the minimal variation in their intensity and peak height indicated that the biofilms had reached a relatively stable state. The biofilms in turn provided a stable microbial substrate and energetic support for the subsequent efficient synthesis of PHA. During the early phase, the dual-function bacteria, such as Pseudomonas, Bacillus, Acinetobacter and Desulfosarcina, prioritized electron transfer and bioelectricity production using available carbon sources. As bioelectricity generation became less critical in the later phase, the bacteria shifted to intracellular PHA accumulation, transitioning from bioelectricity production to PHA biosynthesis. Finally, a comprehensive network connecting functional microorganisms with bioelectricity production, PHA content, TPHC biodegradation, VFA production and EPS peak height was established. Overall, these findings provided valuable insights into the dynamic interactions and metabolic strategies of electroactive biofilms in WMFCs, highlighting their potential for the efficient bioconversion of PHCs into PHAs.